1338 Bariatric Surgery as a Viable Treatment for Idiopathic Intracranial Hypertension: A Case Series. (12th October 2021) - Mahendran, V; Ricart, P; Wadley, M; Perry, A; Robinson, S
Abstract: Introduction: Idiopathic Intracranial Hypertension (IIH) is a significant cause of preventable blindness. Patients also suffer from debilitating headaches, pulsatile tinnitus, nausea, vomiting, photophobia, and radicular pain. If IIH continues to rise as predicted, treatment cost will increase to 462.7 million GBP annually by 2030. Weight loss is the only proven disease-modifying therapy for reversal of IIH. Bariatric surgery is an attractive treatment option due to superlative weight loss and reversal of related comorbidities. The case series aims to raise awareness of bariatric surgery as a safe and effective treatment modality for IIH. Method: The case series consists of a retrospective analysis of four patients with a pre-operative diagnosis of IIH. They were referred to our department for bariatric surgery between January to December 2018. They were followed up for a total of two years. Results: In our case series, all four patients were females with a mean age of 34 years. Mean BMI reduced from 47.3 kg/m2 before surgery to 30 kg/m2 with an EWL of 76.4% at the end of two years after surgery. They all showed significant improvement or resolution in their symptoms related to IIH, and none of them required further CSF pressure reducing procedures afterwards. Conclusions: Bariatric surgery is a safe and effective method of treating IIH. It is superior compared to medical management and CSF pressure reducing procedures which have high rates of recurrence.